Projections of the Sea Level Rise and Sea Surface Temperature of Pars Sea Region Under SSPs Scenarios - Mansuoreh Kohi; Iman Babaeian (Nīvār)
The Arabian Sea is a region of the northern Indian Ocean. The Arabian Sea's surface area is about 3,862,000 km2. The maximum width of the sea is approximately 2,400 km, and its maximum depth is 4,652 meters. The biggest river flowing into the sea is the Indus River. The Persian Gulf is a semi-enclosed epicontinental water body that is located at the northwestern corner of the Indian Ocean. The basin is connected to the Arabian Sea and the Gulf of Oman via the Strait of Hormuz. These water bodies were called Pars Sea. Sea surface temperatures of Persian gulf can exceed 35°C in summer ,while in winter the temperature can fall to <10°C. These regions contributes significantly to current climate change, and suffers deeply from the consequences of this phenomenon. Changes in sea surface temperature (SST) and sea level rise (SLR) affect all forms of life. Therefore, this research aims to project the sea temperature changes of the Arabian Sea and the Persian Gulf, as well as the changes in the sea level of the Persian Gulf and the Oman Sea, based on the output of the CMIP6 under SSPs scenarios for the period 2021-2040.